Can we change binge eating behaviour by interventions addressing food-related impulsivity? A systematic review - Başak İnce (Journal of Eating Disorders, 2021)
Abstract Background An extensive amount of research has underlined the potential role of impulsivity in the development and maintenance of binge eating behaviour. Food-related impulsivity has particularly received attention given its close relationship with overeating and binge eating episodes. Besides the available evidence, our understanding regarding the effectiveness of treatment modalities for binge eating targeting impulsivity and related constructs (e.g., food craving, inhibitory control, and reward sensitivity) is limited. Thus, this systematic review aimed to investigate whether binge eating behaviour is changeable by interventions that are impulsivity-focused and food-related and whether one of these interventions is superior to the others. Method A search on PubMed and PsycINFO was performed for relevant articles published up to September 2020. Studies delivering food-related impulsivity treatment to individuals suffering from binge eating episodes and including a control condition without this treatment were investigated. Following the search, 15 studies meeting the eligibility criteria were analysed. Results Analyses revealed that available impulsivity-focused approaches can be categorised as psychotherapy, pharmacotherapy, computer-assisted cognitive training, and direct neuromodulation interventions. Regarding their effectiveness, it appeared that all of these approaches might be promising to change food-related impulsivity in individuals with binge eating episodes, particularly to decrease binge eating symptoms. However, a superior intervention approach in this early state of evidence could not be determined, although food-related cue exposure, transcranial direct current stimulation, and the combination of several interventions seem fruitful. Conclusion Efforts to treat binge eating behaviour with interventions focusing on food-related impulsivity appear to be promising, particularly concerning binge eating frequency, and also for food craving and inhibitory control. Given limited research and varying methods, it was not possible to conclude whether one impulsivity-focused intervention can be considered superior to others.